Penilaian Kinerja Koperasi Simpan Pinjam Ditinjau Dari Laporan Keuangan (Studi Pada KSP Karya Bakti) - Sri Ayu Febrianti; I Gusti Ayu Oka Netrawati (Jurnal Ilmiah Hospitality, 2022)
This study aims to determine the performance of the Karya Bakti Savings and Loans Cooperative in the period 2019-2021 by analyzing the cooperative's financial statements through a three ratio approach, namely the liquidity ratio (current ratio), solvency ratio (Debt to Total Equity Ratio (DER), Debt to Total Assets Ratio), and profitability ratios (Return on Assets, Return on Equity, Net Profit Margin). The type of research used is quantitative description. The object used in this study is the financial statements for the period 2019-2021. The data analysis method used is quantitative method. he results showed that the performance of the Karya Bakti Savings and Loans Cooperative was in a good category with details, namely, first, based on the results of the liquidity ratio analysis, it showed that the Karya Bakti Savings and Loan Cooperative had very poor criteria with an average value of 1162.28%. econd, the results of the solvency ratio analysis based on the DER value show that the Karya Bakti Savings and Loans Cooperative has very good criteria with an average value of 8.81% and when viewed from the DAR value it has an average value of 8.61%. Third, the results of the profitability ratio analysis based on the ROA value indicate that the Karya Bakti Savings and Loans Cooperative has good criteria with an average value of 7.44%, the ROE value indicates that the cooperative is classified as poor with an average value of 7.62% and the performance of the Savings Cooperative Loans of Work Bakti seen based on NPM are classified as very good with an average value of 64.22%. Thus it can be concluded that overall the Karya Bakti Savings and Loans Cooperative has a good performance and effectively and efficiently can be said to be very good in the use of cooperative capital and it is hoped that the cooperative management can maintain its financial management.